Why Students Should Be Taught Differently: Learner Characteristics, Learning Styles and Simulation Performance. (February 2022) - Kulkarni, Bindu; Banerjee, Ranjan; Raghunathan, Rajasekaran
Background: Business simulation as an instructional tool helps in developing integrative thinking and decision making skills. It is being taught to audiences who differ considerably in age, work experience (learner characteristics) and learning styles. The use of simulations is likely to grow further with advancements in internet technology and the fact that simulations are very amenable to remote modes of instruction. Aim: This study aims to assess how learner characteristics and learning styles impact business simulation performance. It further assesses the combined effect of learner characteristics and learning styles on performance in business simulations, we specifically consider the manner in which learning styles moderate the impact of learner characteristics (age) on simulation performance. Method: The study was conducted with 605 students of full time MBA and executive MBA programs with age group varying from 21 years to 53 years. They were taught using the same business simulation by CAPSIM. The learning styles were measured using Felder-Solomon's instrument 'Index of learning style'. Regression analysis was conducted with predictor variables of learner characteristics and learning styles and outcome variable of simulation performance. The moderating effect of specific learning styles on learner characteristics was identified. Results: The findings indicate that age is a significant predictor of simulation performance (younger, tech savvy students do better). Also, the use of reflective learning style enables better performance in business simulations. Older students are able to draw on experience and benefit more from reflective learning, for business simulations which involve integration across functions. Conclusion: The study enhances our conceptual understanding of the factors enabling performance in business simulations and provides specific direction on how instructors must adapt facilitation approaches for different age groups of participants. Reflection is important for learning with business simulations; hence, the reflective learning style should be encouraged particularly among older students.